Hight school students' beliefs about self-directed english language learning - Tran, Thi Ngoc Thanh (Cantho University, 2014)
This study aims to identify what high school students' beliefs about SDELL are, and explore which factors affect their beliefs. The findings therefore gained from the research are believed to yield several valuable benefits